Entre sofrimento e prazer : a organização do trabalho que vivencia o suicídio - Sartori, Silvanir Destefani (2017)
This is a qualitative approach study in the light of Psychodynamics of Work aiming to understand defense strategies developed by workers in an organization due to suffering originated from attending occurrences involving suicide and/or attempted suicide.